INVESTMENT BEHAVIOUR AND RISKTAKING ABILITY AMONG RETAIL INVESTOR: ROLE OF DEMOGRAPHIC FACTORS - Dr. Rupesh Roshan Singh , Dr. Mahesh Sarva, Mamta Sharma (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Demography factor has a great influence in determining the risk-taking ability among the retail investor which has an ultimate effect on the investment option taken by them. This research paper focuses on understanding the behaviour of retail investor on the basis of demography i.e. age, gender, educational qualification, family, income and so on, and on the basis of these factor which investment option is suitable for which type of investor as investor is categories into 3 different categories i.e. risk taker, risk averse, risk neutral. Primary data is collected with a sample size 200 on the Judgemental non random sampling techniques using the Tableau and SPSS software for analysis of the data through different visualizations and by applying the z- test. In this study it was found that there is direct relationship between demographic factors with risk taking ability among the retail investors which has the direct impact on the investment option. It was found that male are more risk taker as compare to women. The higher the income level retail investor are more likely to take more risk and invest more. Age young aged retail investor are more into investment option as compare to 50's-60's retail investor according to data the young generation 19-35 are investing for capital growth meanwhile the aged investor for saving purpose and in less risky investment option.